Impact of COVID-19 pandemic on families living with autism: An online survey. (October 2022) - Isensee, Corinna; Schmid, Benjamin; Marschik, Peter B.; Zhang, Dajie; Poustka, Luise
Abstract: Background: The current SARS-CoV-2 global pandemic presents a great challenge for governments, health care professionals and the general population. Individuals with autism spectrum disorder (ASD) might be especially vulnerable to restrictions imposed by the crisis. Aim: The objective of the study was to examine the impact of the SARSCoV- 2 pandemic on children with ASD and their families. Methods and procedures: We conducted an online survey two months after the beginning of lock-down (18th of May to 5th of July 2020) in Germany and Austria. We investigated behavioral and emotional changes of children related to the lock-down alongside parental stress and intrafamilial burden Outcome and results: Of the 216 participating families with an autistic child (mean age: 12.23 years), nearly 50% reported aggravation of autistic symptoms and heightened parental stress. Families reported discontinuation of therapy, more intrafamilial conflicts and increase of psychopharmacological medication of the child. Conclusions and implications: Our report on short-term detrimental effects of the pandemic calls for thorough investigation of long-term sequalae for children and families Highlights: The pandemic's outbreak exerts a significant impact on the lives of children with autism and their families. Caregivers reported an increase of autistic symptoms, overall psychopathology and intrafamilial conflicts. There is urgent need for low-threshold access to alternative supporting services for families with children with autism.